2017
DOI: 10.1097/md.0000000000008421
|View full text |Cite
|
Sign up to set email alerts
|

The additional benefit of weighted subjective global assessment (SGA) for the predictability of mortality in incident peritoneal dialysis patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…In the present study, we found that malnutrition, as assessed by the seven‐point scale SGA, was a significant and independent determinant of increased mortality. Several prospective studies have also reported that malnutrition, as evaluated by the original and modified versions of the SGA, is independently and strongly associated with overall and cardiovascular mortality in the dialysis population ( 12–15 ) . This association might be partially explained by interactions between multiple risk factors related to malnutrition that are also associated with increased mortality, including inadequate dietary intake ( 41–44 ) , presence of cardiovascular disease ( 2 ) , metabolic acidosis ( 45 ) and, most importantly, systemic inflammation ( 46 ) and oxidative stress ( 36 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that malnutrition, as assessed by the seven‐point scale SGA, was a significant and independent determinant of increased mortality. Several prospective studies have also reported that malnutrition, as evaluated by the original and modified versions of the SGA, is independently and strongly associated with overall and cardiovascular mortality in the dialysis population ( 12–15 ) . This association might be partially explained by interactions between multiple risk factors related to malnutrition that are also associated with increased mortality, including inadequate dietary intake ( 41–44 ) , presence of cardiovascular disease ( 2 ) , metabolic acidosis ( 45 ) and, most importantly, systemic inflammation ( 46 ) and oxidative stress ( 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative and inflammatory processes act synergistically with respect to promoting protein catabolism, muscle wasting and reduced hepatic albumin synthesis, which together lead to the development of malnutrition in the setting of ESKD ( 10,11 ) . Malnutrition, an independent predictor of mortality in the dialysis population ( 12–15 ) , exacerbates the deleterious effects of systemic inflammation and oxidative stress by increasing the susceptibility to infections and cardiovascular disease risk ( 16,17 ) . It therefore appears reasonable to suggest that a vicious cycle between inflammation, oxidative stress and malnutrition may contribute to the poor survival rates observed in persons on dialysis ( 18 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Serum albumin is commonly considered to be a strong predictor of mortality in dialysis patients [5, 6, 9, 15–17]. Prior studies considered time-varying changes in serum albumin levels in examining the relationship of serum albumin level with mortality in dialysis patients [9, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Demographic information and clinical data such as age, gender, smoking status, and comorbidities were collected at the start of HD. Coronary arterial disease (CAD) was defined as a history of angina, myocardial infarction, coronary angioplasty, or coronary artery bypass grafts; cerebrovascular accident (CVA) was defined as a history of transient ischemic attack, stroke, or carotid endarterectomy; and, peripheral arterial disease (PAD) was defined as a history of claudication, any peripheral revascularization procedure, ischemic limb loss, and/or ulceration [19]. Each patient’s medication information was also investigated at baseline.…”
Section: Methodsmentioning
confidence: 99%